2021
DOI: 10.1158/1538-7445.sabcs20-pd4-06
|View full text |Cite
|
Sign up to set email alerts
|

Abstract PD4-06: How often does retrieval of a clipped lymph node change adjuvant therapy recommendations? A prospective consecutive patient cohort

Abstract: Objectives and Rationale: For breast cancer patients receiving neoadjuvant chemotherapy (NAC) and undergoing pre-NAC axillary lymph node biopsy, NCCN guidelines recommend biopsy marker (clip) placement. This recommendation is based on reports that retrieval of the clipped node after NAC minimizes the false negative rate of sentinel lymph node biopsy (SLNB). Prior studies examining this practice in cN1 patients have reported that the clipped node is a non-SLN 20% of the time. There is limited data regarding if … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
1
2
0
2
Order By: Relevance
“…In the current study, additional removal of the TLN to the SLN after PST in breast cancer patients with initially suspicious axillary lymph nodes had an impact on the postoperative recommendation regarding systemic therapy in only one of 63 cases. This confirms the results of a prospective study presented at SABCS 2020, in which TLNB in addition to SLNB did not result in a change in adjuvant systemic therapy in 104 patients [ 14 ]. Contrary to our assumption, the comparatively high proportion of discordant TLN and SLN of 48.8% in the current study and the significantly higher number of removed TAD nodes in these cases also did not result in a greater impact of TLN on systemic therapy after surgery.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the current study, additional removal of the TLN to the SLN after PST in breast cancer patients with initially suspicious axillary lymph nodes had an impact on the postoperative recommendation regarding systemic therapy in only one of 63 cases. This confirms the results of a prospective study presented at SABCS 2020, in which TLNB in addition to SLNB did not result in a change in adjuvant systemic therapy in 104 patients [ 14 ]. Contrary to our assumption, the comparatively high proportion of discordant TLN and SLN of 48.8% in the current study and the significantly higher number of removed TAD nodes in these cases also did not result in a greater impact of TLN on systemic therapy after surgery.…”
Section: Discussionsupporting
confidence: 87%
“…Recently, a study presented at the 2020 San Antonio Breast Cancer Symposium (SABCS) showed that, in 104 breast cancer patients with clinical nodal downstaging after PST, removal of the TLN in addition to SLNB did not result in a change in adjuvant systemic therapy recommendation in any case. However, at least three SLNs were removed in 83% of the cases analyzed and the concordance rate (CR) of TLN and SLN was 83% [ 14 ]. In the German CLIP-study, on average, only 1.6 SLNs were removed, resulting in a CR of 35.7% for SLN and TLN [ 15 ], and in the European multicentric TATTOO study a CR of only 59.7% was determined [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Weiterhin hatte keine der bisher publizierten TAD-Studien einen onkologischen Endpunkt. Eine aktuelle prospektive Kohortenstudie zeigt bei 78 Patientinnen, dass die zusätzliche Entfernung des TLN zum SLN nur in einem Fall dazu führte, dass eine ALND durchgeführt wurde und dies auf die weitere Therapie-Empfehlung keinen Einfluss hatte 27 . Somit bleibt die Frage nach einem akzeptablen Cut-off für die FNR unklar.…”
Section: üBersichtunclassified
“…Moreover, none of the TAD studies published hitherto had an oncological endpoint. A recent prospective cohort study in 78 patients shows that removal of the TLN in addition to the SLN led in only one case to ALND being performed and that this had no influence on the further treatment recommendation 27 . The question of an acceptable cut-off for the FNR thus remains unclear.…”
Section: Overviewmentioning
confidence: 99%
“…Weiterhin hatte keine der bisher publizierten TAD-Studien einen onkologischen Endpunkt. Eine aktuelle prospektive Kohortenstudie zeigt bei 78 Patientinnen, dass die zusätzliche Entfernung des TLN zum SLN nur in einem Fall dazu führte, dass eine ALND durchgeführt wurde und dies auf die weitere Therapieempfehlung keinen Einfluss hatte 27 . Somit bleibt die Frage nach einem akzeptablen Cut-off für die FNR unklar.…”
Section: Ausblickunclassified